Abudance and Diversity of Pest Types on Golden Teak Trees (Tectona grandis linn. F.) in Pune Village, Galela District - Z. Erbabley, Baltazar; Manikome, Nonice (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Researchers feel it is necessary to conduct this research. The results of the research will provide answers, provide differences and even novelty in knowledge of the abundance and diversity of pests, so that it can make it easier for farmers to control them. The research method carried out went through several stages such as preparation, location determination, sampling using three fishing techniques: Pitfall trap, yellow sticky trap and net trap. The results of research on the diversity of teak plant pests show a range between 0.52-1.34, namely the low category. The high and low diversity of researchers is guided by the Shannon-Wienner index criteria which categorizes the diversity value of a species (H'), so the results of this study show low category diversity because it has an H' value of less than 1.5. Meanwhile, the highest pest diversity was found at location I with pitfall traps, namely with a diversity index value of 1.34. For the abundance research results, there were three pest species with the highest abundance values in each location, namely the first location, the Neotermes tectonae sp species, the second location, the Lasius fuligunosus sp species. and, the species Valanga nigricornis sp. at the third location.